Apoyo en actividades de construcción de obras de ingeniería civil en INCORDIS S.A.S (2022)
INCORDIS S.A.S. is located at Carrera 15 No 16A 14 OF. 408 in the municipality of Duitama department of Boyacá, which is a company dedicated to the construction of civil engineering works, is currently executing projects districts throughout the country, for this the company requires support in construction activities that are required for its proper execution. This work documents the different activities that were executed as support during the internship process, such as unit price analysis, documentati on required for the bidding process, preparation of reports and technical specifications manuals, calculation of quantities of work with their respective memories and others. The purpose of which is to apply and reinforce the knowledge acquired in the acad